Electrical Energy Monitoring and Control System In Boarding Rooms Based On The Internet of Things - Nuryawan Nuryawan; Misbahul Jannah (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Electrical energy is an essential requirement in various activities today. Almost all electronic devices that are used require electrical energy to operate. Therefore, the public needs to know how much electrical energy is used to maintain the quality of electronic devices. Electrical energy monitoring is a process of monitoring and a source of information on electrical energy that can be viewed directly or remotely with real-time output results. Electrical energy monitoring is designed as a routine process of collecting or measuring information source data that determines the level of electricity consumption achievement in real-time. By using real-time information technology, the operating conditions of the hardware system and programs have clear timeframes. Based on this background, the authors want to conduct research designed to monitor and obtain sources of information on the results of the use of electrical energy in boarding rooms, of course this monitoring tool is based on microcontrollers and the Internet of Things (IoT), with the creation of this monitoring of electrical energy, with all parameters electricity such as voltage, current, electric power, electrical energy, and power factor used can be measured using the PZEM-004T sensor. Monitoring electrical energy using the NodeMCU platform as an input and output processor will then be displayed on the control panel display and internet of things (IoT) based Blynk server. From these problems, the authors are interested in conducting research that aims to monitor and obtain sources of information on the use of electrical energy in boarding rooms. This monitoring tool is based on a microcontroller. In addition, this monitoring tool is also based on IoT so that power consumption can be monitored directly and remotely with real-time output results. From the results of the measurement test using the PZEM-004T sensor, it was obtained that the difference in the value of the deviation that occurred was relatively small for voltage 0.538%, current 0.007%, electric power 0.383%, electrical energy 0.005% and power factor 0.039%, it was concluded that the PZEM-004T sensor could be used to further observations. At the same time, the real-time control panel output results to the Blynk server using the NodeMCU ESP8266 produce real-time work, as well as the use of relays as controllers of the tools that have been made, have been tested and obtained satisfactory results.